Pengaruh Pemberian Expressive Writing Therapy Terhadap Penurunan Skor Body Image Distress pada Pasien Kanker Payudara Pasca Mastektomi di Jawa Tengah, Indonesia - Widanti, Nabila Syifa Marta; Kusumadewi, Andrian Fajar; Ismanto, Silas Henry (Jurnal Biomedika dan Kesehatan, 2024)
Background Breast cancer is the most frequently diagnosed cancer worldwide, including in Indonesia, with the highest cancer survivors in Central Java. Mastectomy is one of the procedures in breast cancer treatment which result in major physical and mental alteration, possibly causing Body Image Distress (BID), risking them for depression and suicide. Expressive Writing Therapy (EWT) is an intervention that has been proven to reduce BID in breast cancer patients. Objective: This study aimed to analyze the impact of providing EWT on reducing post-mastectomy breast cancer patients Methods This is an experimental study using a two-group pretest-posttest with CG design conducted on 46 respondents at the oncology surgery clinic at a General Hospital in Central Java. Sample obtained using purposive sampling technique. BID scores were measured using the Body Image Scale (BIS). Data were analyzed in univariate, bivariate, and multivariate analysis using SPSS. Results Data analysis using Mann-Whitney Test showed a significant difference in BID scores reduction between intervention group (IG) and control group (CG) (p=0.00, significance p<0.05). Multivariate analysis using Linear Regression Test showed a significant influence of EWT on reducing BID scores (p=0.00). Conclusions Expressive Writing Therapy (EWT) significantly reduces BID scores in post-mastectomy breast cancer patients in a General Hospital in Central Java, Indonesia.